1985
DOI: 10.3382/ps.0640759
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Grain Amaranth by Broiler Chickens

Abstract: Seed from two species of amaranth (Amaranthus cruentus and A. hypochondriacus) were incorporated into diets at 20 and 40% in raw and autoclaved form. Weight gains of chickens fed diets with 20% amaranth did not differ significantly from that of chickens fed a corn-soybean meal control diet, whether grain was fed raw or autoclaved. Feed intake was reduced slightly at this level of inclusion. Weight gains and feed intake of chickens fed diets containing 40% amaranth were significantly reduced. Reduction in perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…Amaranth, autoclaved for 90 min and incorporated at 40% of the diet, supported body weight gains and feed utilization that were significantly lower (P<.05) than those attained on all other dietary treatments, suggesting that this grain was overcooked. Results of this experiment agree with the report of Waldroup et al (1985). They found that inclusion of amaranth autoclaved at 60 min and incorporated into broiler diets at 20% grew as well and utilized feed as efficiently as those fed a corn-soybean meal control diet.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Amaranth, autoclaved for 90 min and incorporated at 40% of the diet, supported body weight gains and feed utilization that were significantly lower (P<.05) than those attained on all other dietary treatments, suggesting that this grain was overcooked. Results of this experiment agree with the report of Waldroup et al (1985). They found that inclusion of amaranth autoclaved at 60 min and incorporated into broiler diets at 20% grew as well and utilized feed as efficiently as those fed a corn-soybean meal control diet.…”
Section: Resultssupporting
confidence: 93%
“…These results demonstrate that grain amaranth can be sucessfully included in the diet of broiler chickens at levels up to 40% if properly processed by autoclaving or extruding. These findings are in agreement with the studies of Waldroup et al (1985). More studies are needed to assess accurately the exact conditions needed for optimum processing.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, when the data were analyzed separately by location of experiment, the overall interpretation of the data remained the same as expected because the interaction between location of experiment and diet type was not sisnif,tcant. Chicks fed raw A. cruentus tended to performed better than chicks fed raw A. hypochondriacus (Waldroup et al 1985) …”
mentioning
confidence: 97%